2003
DOI: 10.2337/diacare.26.2.285
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Adiponectin Plays an Important Role in Improving Insulin Resistance With Glimepiride in Elderly Type 2 Diabetic Subjects

Abstract: OBJECTIVE—We investigated the effect of glimepiride, a third-generation sulfonylurea hypoglycemic agent, on insulin resistance in elderly patients with type 2 diabetes, in connection with plasma adiponectin and 8-epi-prostagrandin F2α (8-epi-PGF2α), an oxidative stress marker. RESEARCH DESIGN AND METHODS—A total of 17 elderly patients with type 2 diabetes received 12 weeks of treatment with glimepiride. Homeostasis assessment model of insulin resistance (HOMA-IR), homeostasis assessment model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1
18

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 36 publications
1
61
1
18
Order By: Relevance
“…In clinical studies, Tsunekawa et al (41) indicated that glimepiride increased plasma adiponectin levels in type 2 diabetic patients, whereas our group and other investigators previously reported that PPAR␥ agonists elevated plasma adiponectin levels in humans (38,42). Thus, the augmenting effect of glimepiride on plasma adiponectin levels in human subjects may be partly accounted for by its PPAR␥ agonist activity.…”
Section: Discussionmentioning
confidence: 77%
“…In clinical studies, Tsunekawa et al (41) indicated that glimepiride increased plasma adiponectin levels in type 2 diabetic patients, whereas our group and other investigators previously reported that PPAR␥ agonists elevated plasma adiponectin levels in humans (38,42). Thus, the augmenting effect of glimepiride on plasma adiponectin levels in human subjects may be partly accounted for by its PPAR␥ agonist activity.…”
Section: Discussionmentioning
confidence: 77%
“…These three sulfonylureas may doi: 10.7243/2050-0866-7-1 have different effects on the metabolic system. For example, gliclazide has been demonstrated to directly improve oxidative stress and inflammatory cytokine levels [8,9], whereas glimepiride reportedly promotes glucose uptake at the peripheral tissue level and improves insulin resistance [10]. In other words, presumably sulfonylureas probably lower blood PAI-1 levels by suppressing inflammatory cytokines, oxidative stress, and insulin resistance; however, we hypothesized that the effect of these three sulfonylureas on blood PAI-1 levels could differ depending on the drug (drug-effect).…”
Section: Introductionmentioning
confidence: 79%
“…Whether the increased p-adiponectin concentration should be considered secondary to improvement in the metabolic syndrome or whether adiponectin has a primary role in this context cannot be concluded from the current study. Although our extended statistical analysis showed that all changes observed in p-adiponectin were related to changes in its covariates, only a randomized study has the utility to clarify whether adiponectin, by decreasing intramyocellular lipid accumulation (24) and hepatic fat content (25), decreases insulin resistance (26,27).…”
Section: Discussionmentioning
confidence: 99%